Reintegrating extremists: deradicalisation and desistance - Marsden, Sarah V. (Palgrave Macmillan, 2017)
Reducing risk and encouraging desistance -- Supporting agency and facilitating reintegration -- Resilience and belonging -- Redirecting the motivation to offend -- Reintegrating extremists : challenges and opportunities